A new bibliography of writings on varieties of English, 1984 - 1992/93 - Glauser, Beat; Schneider, Edgar W.; Görlach, Manfred (Varieties of English around the world, 1993)
The continuing expansion of research in dialectology, sociolinguistics and English as a world language has made the field increasingly difficult to survey. This bibliography is intended to provide a comprehensive overview of the relevant publications of the past few years. Like its predecessor, it will prove an indispensable reference book. The collection is in four parts, dealing respectively with general studies, Britain and Ireland, the United States and Canada, and the rest of the world. There is a joint index in which the 2800 entries are classified according to specific areas, ethnic gro